2017
DOI: 10.1002/epi4.12054
|View full text |Cite
|
Sign up to set email alerts
|

Onchocerciasis‐associated epilepsy: From recent epidemiological and clinical findings to policy implications

Abstract: SummaryA high prevalence of epilepsy is reported in many onchocerciasis‐endemic regions. In this paper we discuss recent epidemiological and clinical aspects as well as public health implications of onchocerciasis‐associated epilepsy (OAE) and propose a strategy to reduce the burden of disease. OAE probably presents in a variety of clinical manifestations, including the nodding syndrome and the Nakalanga syndrome. The most common clinical presentation, however, is generalized (primarily tonic‐clonic) seizures.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
67
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 61 publications
(70 citation statements)
references
References 43 publications
3
67
0
Order By: Relevance
“…In most PWE, no obvious other cause could be identified and their psycho-motoric development before the onset of seizures had been normal. The peak onset of epilepsy between the ages of seven and 16 years is a characteristic of OAE as observed elsewhere in Africa (Colebunders et al, 2016b(Colebunders et al, , 2017 when they became heavily infected with O. volvulus at a young age. An argument for this hypothesis is a recent study in South Sudan which showed that the age at onset of nodding seizures was around eight years, while the age of other forms of seizures was around 10 years (Colebunders et al, 2018).…”
Section: Discussionsupporting
confidence: 52%
“…In most PWE, no obvious other cause could be identified and their psycho-motoric development before the onset of seizures had been normal. The peak onset of epilepsy between the ages of seven and 16 years is a characteristic of OAE as observed elsewhere in Africa (Colebunders et al, 2016b(Colebunders et al, , 2017 when they became heavily infected with O. volvulus at a young age. An argument for this hypothesis is a recent study in South Sudan which showed that the age at onset of nodding seizures was around eight years, while the age of other forms of seizures was around 10 years (Colebunders et al, 2018).…”
Section: Discussionsupporting
confidence: 52%
“…In 414 of the 486 (85.2%) PWE for which data were available on all OAE criteria, OAE criteria were met. Seventy two PWE were not considered to have OAE for one or more of the following reasons: in 34 (47.2%) the seizures did not start between the ages of 3-18 years; and in 38 (52.7%) the medical history revealed a possible cause of epilepsy, including a perinatal event [1], measles [7], malaria [29] and head injury [3]. An additional 14 infants less than 3 years old also met the OAE criteria when the age of onset of epilepsy and duration of living in the village were not taken into account.…”
Section: Resultsmentioning
confidence: 99%
“…Nodding syndrome (NS) is a neurological disorder that manifests with a unique epilepsy type characterized by repeated head nodding, often in association with progressive neurocognitive impairment and physical decline [1][2][3]. It has been suggested that NS should be considered as one of the clinical presentations of onchocerciasisassociated epilepsy (OAE) [4,5]. However, the pathophysiology of how Onchocerca volvulus may cause epilepsy remains unknown.…”
Section: Introductionmentioning
confidence: 99%